Study of Prevalence of Sexually Transmitted Infection in Patients with Symptoms of Urinary Tract Infection - Sthapit, Rekha; Acharya, Ramesh Prasad; Prasad, Pratap Narayan (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Urinary tract infections are commonly encountered in day to day practice of a general practitioner.The purpose of this study is to determine if there is an association between urinary tract infections (UTI) and sexually transmitted infections (STI), as both may present with similar symptoms. Methods: This was a hospital based, prospective observational study in 104 women of 18 to 49 years age group, done during a period of six months at Patan hospital .Urinalysis results and genital examination findings were recorded.STI was defined as a vaginal swab positive for Trichomonas vaginalis(TV)/Neisseria gonorrhoeae (NG)/Chlamydia trachomatis(CT).UTI was defined as urinary WBC >=6per high power film. A urine c/s >105 colonies of a single pathogen was considered urine culture positive. Results: Mean age of patients was 28.38 years. The most prevalent organism was TV (6/104, 5.8%), followed by NG(4/104,3.8%) and CT(2/104, 1.2%). 11.5% of women had STI , while 57.7% were urine culture positive. Out of those with urine culture positive, 83.3% had urinary WBC<30/hpf , and 16.7% had urinary WBC> 30/hpf. The relation between pyuria and urine c/s positivity was significant ( p value 0.005). The prevalence of STI in urine c/s positive group was 13.3%, and in urine c/s negative group was 9.1% ( p value 0.553). Conclusion: There was no statistically significant difference in the prevalence of STI between urine culture positive and negative groups.